More on Volumes of Revolution 4

Calculus Level 3

When the curve f ( y ) = 25 64 y 2 f(y) = \dfrac{25}{64}y^2 on the interval [ 8 5 5 1 2 , 8 5 5 1 2 ] [\dfrac{-8}{5}\sqrt{\dfrac{\sqrt{5} - 1}{2}}, \dfrac{8}{5}\sqrt{\dfrac{\sqrt{5} - 1}{2}}] is reflected about the line x = 5 1 2 x = \dfrac{\sqrt{5} - 1}{2} a closed region is formed.If the region formed is revolved about the y y axis the volume V = a 4 a b c ( b 1 ) b a π V = \dfrac{a^4\sqrt{a}}{bc}(\sqrt{b} - 1)^{\dfrac{b}{a}}\pi , where a , b a,b and c c are coprime positive integers.

Find a + b + c a + b + c .


The answer is 10.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Mar 12, 2018

Upon reflecting the curve f ( y ) = 25 64 y 2 f(y) = \dfrac{25}{64}y^2 on the interval [ 8 5 5 1 2 , 8 5 5 1 2 ] [\dfrac{-8}{5}\sqrt{\dfrac{\sqrt{5} - 1}{2}}, \dfrac{8}{5}\sqrt{\dfrac{\sqrt{5} - 1}{2}}] about the line x = 5 1 2 x = \dfrac{\sqrt{5} - 1}{2} we obtain the curve g ( y ) = 5 1 25 64 y 2 g(y) = \sqrt{5} - 1 - \dfrac{25}{64}y^2 .

Let j = 5 1 j = \sqrt{5} - 1 and a = 8 5 j 2 a = \dfrac{8}{5}\sqrt{\dfrac{j}{2}} .

The volume V = π a a ( g ( y ) ) 2 ( f ( y ) ) 2 d y = π a a ( j 25 64 y 2 ) 2 ( 25 64 ) 2 y 4 d y = V = \pi \int_{-a}^{a} (g(y))^2 - (f(y))^2 dy = \pi \int_{-a}^{a} (j - \dfrac{25}{64}y^2)^2 - (\dfrac{25}{64})^2 y^4 dy = π j a a ( j 25 64 y 2 ) d y = π j ( j y 25 96 y 3 ) a a = \pi j \int_{-a}^{a} (j - \dfrac{25}{64}y^2) dy = \pi j (jy - \dfrac{25}{96}y^3)|_{-a}^{a} = 2 π a j ( j 25 96 a 2 ) = 2\pi aj(j - \dfrac{25}{96}a^2) = 2 π a j ( j 2 3 j ) = 4 3 j 2 a π = 2\pi aj(j - \dfrac{2}{3}j) = \dfrac{4}{3}j^2a\pi =

16 15 2 j 5 2 π = 16 15 2 ( 5 1 ) 5 2 π = \dfrac{16}{15}\sqrt{2} j^{\dfrac{5}{2}}\pi = \dfrac{16}{15}\sqrt{2}(\sqrt{5} - 1)^{\dfrac{5}{2}}\pi = 2 4 5 3 2 ( 5 1 ) 5 2 π = a 4 a b c ( b 1 ) b a π a + b + c = 10 \dfrac{2^4}{5 * 3}\sqrt{2}(\sqrt{5} - 1)^{\dfrac{5}{2}}\pi = \dfrac{a^4\sqrt{a}}{bc}(\sqrt{b} - 1)^{\dfrac{b}{a}}\pi \implies a + b + c = \boxed{10} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...